Halal Emotional Attachment on Repurchase Intention - Ika Yoga (Shirkah: Journal of Economics and Business, 2018)
This research examines the position of emotional attachment as a mediation of the influence between halal awareness, halal logos and food ingredients composition on repurchase intention of buying halal products. This research brings sample of those who have consumed or have purchased halal products. Due to the population is unknown, by using the Lameshow formula, a total of 384 respondents were obtained. Halal emotional attachment, as this research shows, is able to play a salient role as a mediator of the influence among three aforementioned variables on repurchase intention.Â  This research would have been an effort to contribute marketing halal products as a new concept of the emotional attachment.Â Keywords: halal, Lameshow, marketing halal, repurchase intentionÂ